Global prevalence of colistin resistance in clinical isolates of Acinetobacter baumannii: A systematic review and meta-analysis - Pormohammad, Ali; Mehdinejadiani, Kobra; Gholizadeh, Pourya; Nasiri, Mohammad Javad; Mohtavinejad, Naser; Dadashi, Masoud; Karimaei, Samira; Safari, Hossein; Azimi, Taher (Microbial pathogenesis, 2020)
Acinetobacter baumannii antimicrobial resistance is a public health concern in developing and developed countries, especially in the hospital setting. Understanding the antibiotic resistance profile can help to provide better guidelines for the prescription of appropriate antibiotics, reduction of antibiotic resistance, and introducing new and effective treatment options. Using the PRISMA guidelines, databases of PubMed, Embase, and Cochrane Library were searched systematically from January 1, 2000, to January 1, 2018. All statistical analyses were carried out via Comprehensive Meta-Analysis Software Version 2.0 (Biostat, Englewood, NJ). Depending on the heterogeneity test, either random or fix effect models were used for determining the pooled prevalence of drug resistance. A total of 150 studies were included from 41 countries of six different WHO regional offices worldwide. The highest and the lowest rate of resistance were observed for cefotaxime (99%, 95% CI: 95–99.9) in Africa and colistin (1.1%, 95% CI: 0.3–4.5) in Western Pacific, respectively. Lebanon (17.5%, 95% CI: 16–19) and China (12%, 95% CI: 3.5–32.5) had the highest and Germany (0.2%, 95% CI: 0–2.5) had the lowest rate of resistance for colistin. Conclusion: Our analysis showed that prevalence and rate of increased colistin resistance in South-East Asia and Eastern Mediterranean countries are higher than other regions of the world. Therefore, the establishment of appropriate antibiotic usage guidelines should be essential in these countries. •The highest and the lowest rate of resistance were observed for cefotaxime (99%) in Africa and colistin (1.1%) in Western Pacific, respectively.•Lebanon (17.5%) and China (12%) had the highest and Germany (0.2%) had the lowest rate of resistance for colistin.•Our analysis showed, rate of colistin resistance increase in South-East Asia and Eastern Mediterranean are higher than other regions.